A note on downward inflexibility of prices and the origin of the term «oligopoly» in Thomas More’s utopia - Chelala, Santiago (2011)
This research note aims to present the context in which the term oligopoly has been coined and show the intimate relationship between the origin of the word and downward rigidity of prices, a fundamental phenomenon for economic theory.